Kendala-Kendala Yang Dihadapi Alumni Prodi Pendidikan Ekonomi FKIP UNSYIAH Dalam Mencari Pekerjaan - Agustia Randa; TM Jamil; Ruaida Ruaida (Universitas Syiah Kuala, 2019)
The Puspose of this study is to fond out the problems (1) to describe the busmess dond by greduation of family econury program in economy frenty traning and education of Syiah Kuala University and (2) to deseribe the effots undertaker by the graduation Syiah Kuala University to get a job. This rescareh usiry a qualitative approach with descriptive reseach, sample in this researh consist of 10 people respondents and 5 respoondets take cooperative regyiremeants in accomting the data colletion in this research sweh as guestionaise, observation sheefs, documentation and library study, based on the results of the research cave be known that contans to set a job by the graduation. Lanck of employmeur by graduation of education. Liketation of motor facibilitias and information seeking tools, and lack of cognitive knowledge, profesional fielas, terms and condition of the bidders are still not able be met by the graduation of economic education and the final grade of the cumulative achievement index.The efforts undertaker by the graduation of Syiah Kuala University economic faculty underkater framing and education family economic to fet a job sech as fanding and obtaming telated the information find and get information about spening job vacancies trening fo improve the seientific profession reguised by job appdicants. Willing to work in institution that ase not in accordane wath the profession thay have, choosung a place of hue in the city Banda Aceh city because job and job related casier information to set and continve education to a highev level such as magister.